Development of the Bustanul Athfal Aisyiyah Pijeran II Ponorogo Play Environment in Improving Cognitive Development and Creativity in Childhood - Rizki Dwi Ardika; Sudarno; Bambang Wahrudin; Wiguh Eko Adha Riantiarno; Anik Rachmawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Bustanul Athfal (BA) Aisyiyah Pijeran II is located in Pijeran Village, Siman District, Ponorogo Regency. What used to be community land has now been converted into a learning place for early childhood with the approval of the local community. Apart from being a place to study, this place is also useful as a children's play area with fun games. Games are a tool that must be present in the early childhood education environment. Good rides will have a positive impact on children. This community service program aims to develop a play environment so that children can train emotionally, build creativity, hone thinking skills and foster children's sense of courage. Activity methods in community service include field surveys, selecting designs and making technical drawings, calculating material requirements and designing prototypes. The results of this prototype design produce a swing design that is equipped with a safety system, so that children can play comfortably and without worrying about falling. Apart from that, the addition of play rides in the form of swings on empty land can be beneficial for children so they are interested and feel at home in the play environment for a long time. Properly assembling and installing the position of the swing play ride can create a play ride that is safe and fun for children.